Being somebody & Black besides an untold memoir of midcentury Black life - Nesbitt, George B. 1912-2002 (The University of Chicago Press, 2021)
"Like many twentieth-century Black families, the Nesbitts achieved an incredible transformation over the course of a single generation: from performing manual labor on the rural farms of the deep south to holding advanced degrees and owning property in the urban midwest, their family's story was lived or dreamed of by many who moved north during the Great Migration. In Being Somebody and Black Besides, George B. Nesbitt recounts the extraordinary struggles he, his parents, and his five siblings faced in their upwardly mobile journey from the Great Migration through the Freedom Struggle. Born in Champaign, Illinois, Nesbitt earned a law degree at the University of Illinois, enduring racist lectures and administrators who sought to penalize him when he advocated for racial equality. After graduating, he served in World War II, facing discrimination and harassment like many Black soldiers. And when the war was over, despite his education he held many jobs, some quite lowly, before he became deputy assistant to the secretary of Housing and Urban Development in the Kennedy administration. A keen observer and narrator of race, Nesbitt recounts with righteous and justified anger his bitter struggles and incredible triumphs, shared by Black men and women in America. His beautifully written memoir is a rare example of a sustained first-person narrative about Black life in this era. While many of his experiences will resonate with today's readers, others will provide a crucial glimpse into a chapter of Black life and its place in the unfinished struggle for racial justice in our country"--
Keywords: Nesbitt, George B. / 1912-2002; African Americans / Biography; African Americans / Illinois / Biography; African American lawyers / Biography; Civil rights workers / United States / Biography; African Americans / History / 20th century; Race discrimination / United States / History / 20th century; African American lawyers; African Americans; Civil rights workers; Race discrimination; Illinois; United States; 1900-1999; Autobiographies; Biographies; History